From lifelong learning to youth employment: back to the future for higher education in Scotland's colleges. Issue 3 (3rd May 2016) - Lowe, Janet; Gayle, Vernon
Abstract : This article explores aspects of the experience of higher education students in a Scottish college within the context of widespread contemporary concern about youth unemployment. Analysis of published data reveals a marked shift in the demographic profile of higher education students in colleges in favour of young people. An unseen consequence of this change has been a decline in opportunities for older students, particularly women wishing to study part time at an advanced level. Survey data from one college follows up an earlier case study and explores new dimensions of the work/life/study balance. In this study the respective experiences of school leavers, young adults and adults are compared. Over half of the students were in paid work, an increase compared with the previous survey. The relationship between work or family life and study was significant in influencing the quality of the students' experience. Young part-time students, many of whom were following modern apprenticeships, achieved a more successful work/life/study balance compared with full-time students who were in paid work. It is recommended that colleges should devote attention to enabling students to maximise the benefits of combining work with study, to prepare them for transition into a difficult labour market. It is also argued that the different priorities of older lifelong learners should continue to be recognised as their numbers decline.